2018
DOI: 10.1088/1742-6596/1028/1/012151
|View full text |Cite
|
Sign up to set email alerts
|

Pointing Gesture and Speech of Teachers in Mathematics Learning Accordingto Information, Initiation, and Feedback

Abstract: Abstrack. The purpose of this research is to describe the pointing gesture and teacher's speech SMPN 2 and SMPN 4 Ternate in learning mathematics accordingto information, initiation and feedback. Pointing gesture forms an integrated system with assertive and directive speech and contributes to mathematics learning. Information as an explanation in the conversation and example. Initiation in classroom conversation is a form of opening speech as a trigger/stimulus performed by the teacher with the aim of obtaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
1
0
6
Order By: Relevance
“…Gestures can be in the form of gestures either from the fingers, hands, arms, or other body parts that accompany spoken communication to emphasize and reduce the ambiguity of the information conveyed (Damayanti, 2018;Ibraheem & Khan, 2012). In this study, the type of gesture observed was the one developed by Alibali and Nathan (2012) and Ruhama et al (2018) which includes (1) pointing gesture, that is the motion of pointing to an object, subject, or place with fingers, writing tools, or other pointing tools; (2) representational gesture, that is a motion that represents objects, concepts, relations with the intention that can be understood by other people; and (3) writing gesture, that is a writing motion that occurs simultaneously with speech. The three types of gestures were chosen because, in the study process, the three gestures are easy to observe and suitable for analyzing the student generalization process.…”
Section: Introductionmentioning
confidence: 93%
“…Gestures can be in the form of gestures either from the fingers, hands, arms, or other body parts that accompany spoken communication to emphasize and reduce the ambiguity of the information conveyed (Damayanti, 2018;Ibraheem & Khan, 2012). In this study, the type of gesture observed was the one developed by Alibali and Nathan (2012) and Ruhama et al (2018) which includes (1) pointing gesture, that is the motion of pointing to an object, subject, or place with fingers, writing tools, or other pointing tools; (2) representational gesture, that is a motion that represents objects, concepts, relations with the intention that can be understood by other people; and (3) writing gesture, that is a writing motion that occurs simultaneously with speech. The three types of gestures were chosen because, in the study process, the three gestures are easy to observe and suitable for analyzing the student generalization process.…”
Section: Introductionmentioning
confidence: 93%
“…] (a), dan [5] (e). Guru menggunakan pointing gesture disertai pertanyaan untuk memperoleh jawaban atau respon siswa dalam pembelajaran matematika (Ruhama et al, 2018).…”
Section: Penggalan Percakapan [2]unclassified
“…Dikatakan respon verbal karena siswa sudah mengetahui dengan mudah jawaban dari pengalaman dan pengetahuan yang diperoleh pada pembelajaran di sekolah sebelumnya (Ruhama, 2019).Terjadinya respon verbal siswa disebabkan juga siswa telah menggunakan pointing disertai tuturan untuk merespon jawaban siswa dan membantu pemahaman siswa (Alibali & Nathan, 2007). Guru menggunakan pointing gesture untuk membenarkan atau menegaskan dan menjabarkan jawaban siswa di papan tulis (Ruhama et al, 2018). Guru menggunakan pointing gesture danmembenarkanatau menegaskan jawaban siswa Mustafa A.H. Ruhama 1 , Marwia Tamrin Bakar 2 untuk memfokuskan perhatian siswa agar memudahkan siswa memahami materi matematika (Ruhama, 2019).…”
Section: Penggalan Percakapan [2]unclassified
See 1 more Smart Citation
“…Gesture dalam penelitian ini berfokus pada gerakan tangan atau alat yang digunakan untuk memunculkan ide dan pikiran. Menurut Ruhama et al, (2018) Gesture diklasifikasikan menjadi yaitu pointing gesture (gesture menunjuk), representational gesture (gesture representasi) dan writing gesture (gesture menulis). Penelitian ini hanya merujuk dua pengklasifikasian yaitu Pointing gesture dan Representational gesture.…”
unclassified